ANALISIS FINANCIAL DISTRESS PADA PT. INDOSAT TBK DENGAN MENGGUNAKAN METODE ALTMAN (Z-SCORE) DAN METODE SPRINGATE (S-SCORE) - Nurul Febrianti Anti; Aris Munandar (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
The purpose of this study was to determine and analyze the prediction of financial difficulties at PT. Indosat Tbk, which is listed on the Indonesia Stock Exchange for the 2010-2019 period, uses the Altman Z-score and Springate S-score methods. This study uses secondary data, namely the annual financial statements of the Indosat Tbk Company for the period 2010-2019 using document recording techniques and analyzed using the Altman Z-score and Springate S-score methods. The final results of this study indicate that the financial performance analyzed by the Altman Z-Score method at the Indosat Tbk Company for the 2010-2019 period is classified as not experiencing financial difficulties or experiencing no financial distress. The final results of this study indicate that the financial performance analyzed using the Springate S-score method at Indosat Tbk Company for the 2010-2019 period is classified as experiencing financial difficulties or experiencing financial distress.Keywords: financial distress, altman z-score, springate s-score method